Evaluation of recalls of FSIS-regulated food products: January 1994 through August 2018 - Sommer, Anna Marie (My University, 2019)
The primary focus of this integrated learning experience project was to evaluate and analyze recalls of FSIS-regulated food products that occurred between January 1994 and August 2018. This evaluation of the data recorded from these recalls is a trend analysis. This analysis characterized the recalls of FSIS-regulated food products in several ways including by: pounds of product recalled, severity of potential health risk (i.e., recall class), facility size, the type of meat product involved, the method by which the recall was initiated, and the reason for the recall. The analysis further evaluated pathogen-related recalls in more depth, particularly those related to shiga toxin-producing Escherichia coli (STEC). During the 24 years and 8 months encompassed by the trend analysis time period (January 1994 through August 2018), there were a total of 1,810 recalls of FSIS-regulated food products. Because the final year of data is an incomplete year, the calendar years of 1994 through 2017 were used to calculate calendar year averages. During the 1994 through 2017 calendar years, there were 1,737 recalls in total with an average of 73 recalls per year. More than 774 million pounds of food products were recalled during the entire study period with 771.3 million pounds of food products recalled from 1994 through 2017 which was used to calculate the average of 32.1 million pounds recalled per calendar year. During the 1994-2017 calendar years, there was an average of 444,070 pounds of food products per recall, with the least number of pounds recalled being 0 pounds and the largest number of pounds recalled in a single recall being 143.4 million pounds. For the entire study period Class I recalls comprised 71% of the total number of recalls whereas Class II represented 21%, and Class III represented 8%. Of the 1,810 recalls, 692 were due to presence of a pathogen, with 21% of those being associated with STEC. Starting in 2004, data regarding the size of a facility (as per HACCP regulations) was documented. Of the 1,052 recalls with specified HACCP facility sizes, 54% were small, 30% were very small, and 16% were large facilities. During the study period, the top 3 reasons for initiation of a recall were the presence of (1) an undeclared allergen, (2) Listeria monocytogenes, and (3) Escherichia coli O157:H7. A total of 264 recalls of FSIS-regulated food products involved STEC. On average, 15% of all recalls of FSIS-regulated food products were associated with STEC for each calendar year from 1994 through 2017. Sixty-one (23%) of the STEC recalls were associated with an illness or outbreak while 203 (77%) of the STEC recalls were not. Of the total number of recalls associated with illness or outbreak (95), 61 of them were associated with STEC (64.2%). Of those recalls associated with STEC for which a HACCP facility size was recorded, from January 2004 through August 2018, 55% were attributed to small facilities, 28% to very small facilities, and 17% to large facilities. From 1994-2010 all recalls attributed to STEC were associated with O157:H7 as that was the only STEC that had been declared an adulterant. In January of 2010, the FSIS begin to more specifically identify those previously categorized as non-O157:H7 by the six serotypes laid out in the new directive. The serotypes that were included in the new directive for serotyping Escherichia coli were O26, O45, O103, O111, O121, and O145. However, they were not formally recognized as adulterants until the directive went into effect in June 4, 2012. The breakdown of post-2010 recalls due to STEC, was O157:H7 70%, O26 7%, O45 3%, O103 8%, O111 1%, O121 4%, and O145 3% with the remaining 3% associated with non-O157:H7 and O157: non-motile.
Keywords: food safety; Escherichia coli; Shiga toxin-producing Escherichia coli,